2020
DOI: 10.1111/jsr.13238
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and fathers’ sleep: Is there a difference between first‐time and experienced parents of 6‐month‐olds?

Abstract: Sleep disruption and deprivation are highly prevalent among parents of an infant. However, most postpartum sleep studies focus solely on mothers, and few studies have investigated whether sleep differs between first‐time and experienced parents. The present study aimed to determine whether self‐reported sleep duration and quality differ between first‐time and experienced mothers and fathers during the postpartum period. A total of 111 parents (54 couples and three single mothers) of 6‐month‐old infants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Gay et al showed in their study that infant feeding was not related to self‐reported sleep disturbance or fatigue for mothers or fathers 3 . More recently, Kenny et al reported that breastfeeding was significantly associated with shorter consecutive nocturnal sleep duration and more nocturnal awakenings in mothers 24 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Gay et al showed in their study that infant feeding was not related to self‐reported sleep disturbance or fatigue for mothers or fathers 3 . More recently, Kenny et al reported that breastfeeding was significantly associated with shorter consecutive nocturnal sleep duration and more nocturnal awakenings in mothers 24 …”
Section: Discussionmentioning
confidence: 97%
“…3 More recently, Kenny et al reported that breastfeeding was significantly associated with shorter consecutive nocturnal sleep duration and more nocturnal awakenings in mothers. 24…”
Section: Discussionmentioning
confidence: 99%
“…Participants completed a demographic questionnaire to obtain information on their age, education level, employment status and number of children. A questionnaire about sleep-related parental practices during the postpartum period (adapted from the Sleep Practices Questionnaire) [32][33][34] was used to assess: (1) infant feeding method (ie, no breast feeding, partial breast feedingmixed feeding or exclusive breast feeding) and ( 2) infant sleep location (ie, solitary or cosleeping). Solitary sleep referred to the infant sleeping in his/her own room either alone or with siblings on a nightly basis, whereas cosleeping was defined as the infant sleeping in the same room as parents (ie, same bed, bassinet or crib).…”
Section: Family Factorsmentioning
confidence: 99%
“…Interestingly, this association was not detectable in fathers. 101 Thus, future research should focus on potential differences between first-time and experienced parents. Furthermore, we only assessed information of parents in heterosexual relationships, thus contributing data of same-sex parents should be assessed in future research.…”
Section: Limitationsmentioning
confidence: 99%